2023
DOI: 10.1055/a-2217-8313
|View full text |Cite
|
Sign up to set email alerts
|

COVID-stasis of Pregnancy: An Increased Prevalence of COVID-19 in Patients with Cholestasis

Marissa G. Holden,
Kathryn V. Schmiech,
Mariana Martinez Telleria
et al.

Abstract: Objective To evaluate the relationship between intrahepatic cholestasis of pregnancy (ICP) and coronavirus disease 2019 (COVID-19). Study Design We performed a retrospective cohort study of pregnant women undergoing induction of labor (IOL) at a single institution between May 2020 to January 2021. Primary exposure was diagnosis of intrahepatic cholestasis of pregnancy (ICP). The primary outcome was the prevalence of COVID-19 as determined by reverse-transcriptase polymerase chain reaction testing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In the latest study on the topic by Holden et al, the authors reported an increased incidence of COVID infection in women with ICP. Among 596 patients, all individuals who tested positive for COVID-19 with ICP were Hispanic [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the latest study on the topic by Holden et al, the authors reported an increased incidence of COVID infection in women with ICP. Among 596 patients, all individuals who tested positive for COVID-19 with ICP were Hispanic [26].…”
Section: Discussionmentioning
confidence: 99%